(untitled) (Analysis of International Sciences, 2023)
Historically, operating systems with network management capabilities were referred to as dedicated network operating systems because they allowed personal computers (PCs) to use computer networks, including handling files and printers within a local area network (LAN). This description of operating systems is of historical importance, as many of these operating systems include a network stack that operates on a client-server model, and we introduce the types of network operating systems.